Large Air Quality and Public Health Impacts due to Amazonian Deforestation Fires in 2019. (26th July 2021) - Butt, Edward W.; Conibear, Luke; Knote, Christoph; Spracklen, Dominick V.
Abstract: Air pollution from Amazon fires has adverse impacts on human health. The number of fires in the Amazon has increased in recent years, but whether this increase was driven by deforestation or climate has not been assessed. We analyzed relationships between fire, deforestation, and climate for the period 2003 to 2019 among selected states across the Brazilian Legal Amazon (BLA). A statistical model including deforestation, precipitation and temperature explained ∼80% of the variability in dry season fire count across states when totaled across the BLA, with positive relationships between fire count and deforestation. We estimate that the increase in deforestation since 2012 increased the dry season fire count in 2019 by 39%. Using a regional chemistry‐climate model combined with exposure‐response associations, we estimate this increase in fire resulted in 3, 400 (95UI: 3, 300–3, 550) additional deaths in 2019 due to increased exposure to particulate air pollution. If deforestation in 2019 had increased to the maximum recorded during 2003–2019, the number of active fire counts would have increased by an additional factor of 2 resulting in 7, 900 (95UI: 7, 600–8, 200) additional premature deaths. Our analysis demonstrates the strong benefits of reduced deforestation on air quality and public health across the Amazon. Plain Language Summary: Exposure to air pollution created from fires in the Amazon fires has detrimental impacts on human health. The number of active fires across the Brazilian Legal Amazon (BLA) has increased in recent years, but the reason for this increase has not been fully assessed to‐date. Using a statistical model, we found that increases in BLA deforestation rate since 2012 increased dry season fire count in 2019 by 39%. Using a regional chemistry‐climate model, we estimated that this increase in fire count resulted in 3, 400 (95UI: 3, 300–3, 550) additional human deaths in 2019 due to increased population exposure to fine particulate matter air pollution. We also found that if deforestation in 2019 had increased to the maximum recorded during 2003–2019, the number of active fires would have increased by an additional factor of 2 resulting in 7, 900 (95UI: 7, 600–8, 200) additional deaths. The findings of our analysis demonstrate the strong benefits of reduced deforestation on air quality and public health across the Amazon region. Key Points: Increases in deforestation among states analyzed in the Brazilian Legal Amazon since 2012 increased the dry season fire count by 39% in 2019 This increase in fire resulted in 3, 400 (3, 300–3, 550) additional deaths in 2019 due to increased exposure to particulate air pollution Our analysis demonstrates the strong benefits of reduced deforestation on air quality and public health across the Amazon